Philadelphia Housing Action: Covid-19 Pandemic and Negotiating our Survival - Johnson, Sterling (PARTECIPAZIONE E CONFLITTO, 2023)
Philadelphia Housing Action is a group of experienced housing organizers formed at the beginning of the Covid-19 pandemic. While the U.S. government made funds available for emergency housing, the city government refused to use it all while continuing to sweep homeless encampments from place to place. In response, Philadelphia Housing Action embarked on a housing takeover campaign to help homeless mothers on the streets using unused vacant public property. To keep the houses, they held space, with a massive encampment in the middle of the city demanding that the houses be delivered to them and for the city to secure safe housing for these vulnerable Black and Latino families.